**Answers:**

3 - (x+5) = 3x + 6

Distribute the -1

3 - x - 5 = 3x + 6

Combine like terms on the left side

-x - 2 = 3x + 6

Subtract 3x from each side

-4x - 2 = 6

Add 2 to each side

-4x = 8

Divide both sides by -4

x = -2

you do know you're supposed to figure this out yourself, right? It's your homework.

I was never good at math but I use webmath.com and it helpos alot. You can put the problem in and it solves it for you plus it shows you how to do it step by step.I hope it works for you to!

3 - (x+5)=3x + 6

-3 -3

-----------------------

-x-5(since da neg. is left u mult. -1 with da parenthesis)=3x+3

+x +x

-------------------------

-5=4x+3

-3 -3

------------

-8=4x

(divide by 4)

-2=x

i hope u understood it!

3 – (x+5) = 3x + 6

=3-5x=3x+6

= -3x -3x

=3-2x=6

1x=6

=

3 - ( x + 5 ) = 3x + 6

- ( x + 5 ) - 3x = 6 - 3

- x - 5 - 3x = 6 - 3

- x - 3x = 6 - 3 + 5

- 4x = 8

x = 8/ -4

x = -2

This article contents is post by this website user, EduQnA.com doesn't promise its accuracy.

**More Questions & Answers...**